2019
DOI: 10.1136/bmjopen-2018-026459
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact, response and preparedness to water-related natural disasters in the Barisal division of Bangladesh: a mixed methods study

Abstract: ObjectivesTo investigate the impact of natural disasters on communities in the Barisal division of Bangladesh, exploring community approaches to disaster preparedness and mitigation.SettingCommunities in all districts of the Barisal division of Bangladesh.ParticipantsQuantitative data were collected through a cross-sectional household survey (n=9263 households; n=38 981 individuals). Qualitative data were collected through in-depth interviews (n=7) and focus group discussions (n=23) with key informants.Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…First, pursuing partnerships in disaster risk reduction with alignment with the Sendai Framework,21 represents the most significant opportunity. Flooding is a major contributor to drowning risk and studies reinforce the need for preparedness for water-related disasters,22 flood rescue training for emergency personnel,23 and risk analysis and early warning systems. Sendai promotes subnational and local government disaster risk reduction planning, where drowning prevention should form part of multihazard approaches to building local disaster resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, pursuing partnerships in disaster risk reduction with alignment with the Sendai Framework,21 represents the most significant opportunity. Flooding is a major contributor to drowning risk and studies reinforce the need for preparedness for water-related disasters,22 flood rescue training for emergency personnel,23 and risk analysis and early warning systems. Sendai promotes subnational and local government disaster risk reduction planning, where drowning prevention should form part of multihazard approaches to building local disaster resilience.…”
Section: Discussionmentioning
confidence: 99%
“…First, pursuing partnerships in disaster risk reduction with alignment with the Sendai Framework, 21 represents the most significant opportunity. Flooding is a major contributor to drowning risk and studies reinforce the need for preparedness for water-related disasters, 22 flood rescue training for emergency personnel, 23 Understanding barriers and expanding investments in locally generated disaster risk data could contribute to and strengthen surveillance for drowning prevention. 24 25 National and community level disaster coordination could be adapted to include mechanisms with potential to extend impacts on drowning prevention outside of disaster events.…”
Section: Positioning Drowning In Other Health and Development Agendasmentioning
confidence: 99%
“…A survey in Bangladesh found that few people evacuate during disasters, indicating a widespread fatalistic view of natural disasters among the local population. Other reasons for not evacuating included fear for the safety of property and livestock, overcrowded shelters, and unsafe places for women (Jagnoor et al, 2019).…”
Section: Disaster Preparednessmentioning
confidence: 99%
“…The urban environment is highly challenged due to unplanned development, drainage congestion, lack of proper solid waste management, and encroachment of rivers, canals, and other water bodies [32]. The city experiences cyclones and flooding (waterlogging, riverine/monsoon flood, and storm/tidal surge) almost every year as its significant natural hazards where anthropogenic causes exacerbate the condition [35,36]. The city has experienced assets and infrastructure damages due to catastrophic cyclones in 1991, 2007, 2009, 2013, 2016, 2020, and 2021 and floods in 1988, 1991, 2004, 2007, 2010, and 2020 in recent times.…”
Section: Risk Profilementioning
confidence: 99%